Performance of the BD Veritor system SARS-CoV-2 antigen test among asymptomatic collegiate athletes: A diagnostic accuracy study - Casey M. Kepczynski; Jaelin A. Genigeski; Daniel P. de Regnier; Emmanuel D. Jadhav; Minji Sohn; Michael E. Klepser (Elsevier, 2021)
Background: COVID-19 testing strategies and determining the accuracy of tests is crucial for the prevention of disease in asymptomatic communities. Objective: To determine the positive predictive value for the BD Veritor System for rapid detection of SARS-CoV-2 (BD Veritor System) among asymptomatic athletes and athletic staff in a University setting. Secondarily, a cost savings analysis was conducted to evaluate the benefits of a rapid antigen testing strategy over a universal PCR-based strategy. Methods: Asymptomatic athletic personnel at Ferris State University tested using the BD Veritor System from November 4, 2020-February 15, 2021. Individuals whose antigen test was positive immediately had specimen collected for confirmatory PCR testing. These results were used to determine the positive predictive value (PPV) for the BD Veritor System. A cost-savings analysis was conducted from the University's perspective to determine the value of this rapid antigen testing strategy over a universal PCR-based strategy. Results: A total of 3352 antigen tests were performed on 359 individuals during the study period. During this period, 21 positive antigen tests were obtained of which 5 individuals had a positive reflex PCR result. The calculated PPV of the BD Veritor System among asymptomatic individuals was 25%. According to the mandated athletics testing schedule, the University spent $67,475.76 on BD Veritor System tests and $1785 on confirmatory PCR tests. In contrast, if a solely PCR-based approach had been continued, the same testing strategy would have cost the University $284,920. By employing a 2-tiered testing strategy with the BD Veritor System with reflex PCR testing, the University realized a cost savings of $215,659.24 during the 3-month period. Conclusions: Despite sub-optimal PPV associated with the BD Veritor System among asymptomatic athletes, the University was able to effectively use an antigen-based testing program to comply with collegiate testing requirements and realize $215,659.24 cost savings per quarter over a PCR-based strategy.